The Effectiveness of Traditional Chinese Yijinjing Qigong Exercise for the Patients With Knee Osteoarthritis on the Pain, Dysfunction, and Mood Disorder: A Pilot Randomized Controlled Trial - Zhang, Shuaipan; Guo, Guangxin; Li, Xing; Yao, Fei; Wu, Zhiwei; Zhu, Qingguang; Fang, Min (Frontiers in Medicine, 2022)
Background: Although traditional Chinese Yijinjing Qigong Exercise (YJJQE) is popularly used to alleviate symptoms in people with knee osteoarthritis (KOA) in China, no randomized controlled trials (RCTs) are available to evaluate the effects of YJJQE in patients with KOA. The purpose of this trial is to assess the clinical efficacy of YJJQE for patients with KOA. Methods: A total of 50 participants clinically diagnosed with KOA are randomly (1:1) assigned to the YJJQE group (n=25) and the stretching training exercise (STE) group (n=25) for a 40-minute exercise session twice a week for 12 weeks. All outcome measures are collected at baseline and 12-week ending intervention, which includes the primary outcome of Western Ontario and McMaster Universities Osteoarthritis Index Scale (WOMAC) and the secondary outcomes of visual analog scale (VAS), mental component summary (MCS), physical component summary (PCS), Beck depression inventory (BDI), perceived stress scale (PSS), Berg balance scale (BBS), and the Gait functional mobility data. Results: The YJJQE group did not have any significant changes compared to the control group on the WOMAC score after the 12-week intervention (P＞0.05), though the YJJQE group demonstrated better performance in MCS, BDI, and PSS (P=0.002, P=0.001, and P=0.026, respectively) than the control group. No serious adverse events occurred in either group, and only mild muscle soreness was reported during both exercise treatments. Conclusion: Because of no difference between both groups as regards the primary outcome measurement (WOMAC), it can hardly explain that the YJJQE had an advantageous effect on the pain and dysfunction of knee osteoarthritis patients. However, compared to the control group, YJJQE appeared to be associated with improvements in psychological well-being including reduced stress, anxiety, depression, and mood disturbance to manage KOA. Further trials with larger sample sizes and follow-up studies were required. This trial was registered in Chinese Clinical Trial Registry (ChiCTR2000037256). URL: https://www.chictr.org.cn/edit.aspx?pid=60357&htm=4.